Analysis of Leading Sectors in Gresik Regency Using the LQ, DLQ, and MRP Methods for the 2020-2024 Period - Anisa Dian Lestari; Afriska Alfiana Nillatul Laili; Della Puji Setyorini; Fahrizal Taufiqqurrachman (Escalate : Economics and Business Journal, 2026)
Abstract: This study aims to analyze the leading sectors of the Gresik Regency economy based on Gross Regional Domestic Product (GRDP) data by business field for the period 20202024. The study uses a quantitative approach with secondary data sourced from the Gresik Regency and East Java Province Central Statistics Agency. The research instrument consists of GRDP data based on constant prices, which is analyzed using the Location Quotient (LQ) method, Dynamic Location Quotient (DLQ) method, and Growth Ratio Model (MRP). The LQ method is used to identify the base sector, DLQ to analyze changes in sectoral advantages dynamically, and MRP to assess sectoral and regional growth performance. The results of the study show that the Manufacturing and Mining and Quarrying sectors are the base sectors with comparative advantages in Gresik Regency. Dynamically, the Manufacturing sector shows more sustainable growth performance compared to other sectors. Meanwhile, some agricultural and service sectors still show relatively lower growth. These findings indicate that the economic structure of Gresik Regency is still concentrated in certain sectors and requires more balanced development policies to promote sustainable regional economic growth.